Accounting and informational aspect of funding amortization policy - Trachova, Dar’ya (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The article analyzes the influence of accounting systems on the formation of depreciation policy. The correlation between increased accounting and reduction of depreciation policy efficiency is monitored. The author's interpretation of the accounting component of the essence of the amortization policy of the enterprise is given, taking into account the features and principles of the financial and economic mechanism of reproduction.Methods. The database of empirical research is the database of Ukrainian companies' registration data, which includes enterprises of various industries and sizes. The article presents the results of research and research prospects for the formation of amortization policy of the enterprise. The information portal of the State Statistics Service of Ukraine was used as a source of data on national trends in the creation and use of a depreciation fund. The methodology of the database is based on theoretical and rational studies. The technique included a questionnaire and a similar analysis of the company’s depreciation policy and the current depreciation of innovations for students, and shock absorbers and innovations for students and students and students and students, and shock absorbers and training for students and students and students and students, but they are deprecated for students and students.Findings. The amortization policy of the state is the basis of the investment, innovation process, as well as one of the most important mechanisms for promoting self-financing policy. In developed countries, state policy on accelerated depreciation has become the main instrument of economic growth. Amortization policy reform should take place both from the inside and from the enterprise at the same time. In the existing components of the formation of the depreciation fund of the enterprise, even at the expense of its own resources, it is impossible and requires the implementation of effective steps of the regulatory and legal regulation of the state. In order to successfully implement the amortization policy reform measures, one must take into account the main requirement of the present-the possession of high-quality and operational information that is relevant to all participants in the process. A quick and transparent interaction between the enterprise, government agencies and manufacturers or technology vendors is a key to the success of this process. The coordination of this process should be carried out by one state structure, which will ensure a unified approach to the method of implementation and control of the calculation and accumulation of reporting information.Research implications. Problems requiring a more detailed study are the formation and implementation of a depreciation policy, the effectiveness of which depends not only on the economic and logistical state of individual enterprises, but also on the welfare of the state as a whole. To make such changes is necessary taking into account the basic requirements for accounting - comparability, accuracy and objectivity, clarity and availability, timeliness, efficiency and rationality. They can achieve the goal of accounting - to provide the management apparatus, relevant services and specialists with the necessary reliable data on business processes and financial condition of the enterprise.Results. When forming a depreciation policy, companies need to have a clear guide to the degree of independence in the formation and use of a depreciation fund. It would be logical to apply increased control measures to the amounts remaining at the disposal of the enterprise after the release from taxation of any state protectionism programs in terms of using the depreciation fund for innovative asset upgrades. Which suggests the creation of a single database, the open information that can be used by all participants in the formation of the enterprise’s depreciation policy.